Assessing the effects of institutions on the ownership structure of MNCs investments in global cities - Moreira da Silva, F.; Pereira, R.; Ogasavara, M. H. (International Business Review, 2024)
This study analyzes the relationship between institutions and ownership in cross-border acquisitions. First, this research contributes to the existing literature by considering the relative position of cities of origin and destination in this relationship and examining the asymmetric effects of institutional distance. Furthermore, we contribute by taking the concept of global cities and analyzing the influence of these locations on ownership decisions in cross-border acquisitions. Using a database with multiple home and host-cities and adopting a binary logistic analysis, the results indicate that MNCs hold a higher stake in the equity of an acquiree located in a developed country, and their commitment of resources to acquisitions in global cities is higher than it is in other cities. These findings suggest that analyzing distance direction is essential, and brings new insights when examined at the subnational level.